Development of Kaffah Learning Model on Fluid Concept to Improve Metacognition, Character, and Scientific Attitude Prospective Teacher Students - Syahrial Ayub; Muhammad Taufik (Lembaga Bale Literasi, 2025)
The objective of this research is to develop the Kaffah learning model, which will be accompanied by supporting tools and learning resources, with the aim of enhancing metacognition, character, and scientific attitudes among students. The supporting components of the Kaffah learning model, which have been developedThe product that will be applied is a product that is already feasible, which is already valid and tested. The research was conducted using the Borg and Gall model development research method, which involved the following steps: research and information collection, planning, developing a preliminary form of the product, preliminary field testing, main product revision, main field testing, operational product revision, operational field testing, final product revision, dissemination and implementation. The response questionnaire of educators and students to the product was utilized to evaluate its practicality. Observation sheets were utilized to assess learning implementation, validity, and reliability. Moderation techniques were employed to evaluate learning and project assessment. Finally, the success of projects made by students was evaluated through the use of a project assessment. The data was subjected to various analyses, including a feasibility test, a practicality test, and an effectiveness test. The latter was conducted using N-Gain, with the results subsequently confirmed by an independent t-test and a multiple analysis of variance (MANOVA) test. The findings demonstrated that the Kaffah learning model, when accompanied by supporting devices and learning, is both valid and reliable. Consequently, it can be concluded that the model is a feasible option for use in learning.